Konsep Islamisasi Sains Matematika dalam Pemikiran Al-Khawarizmi: Sebuah Kajian Teoritis - Alhafidh Nasution, STh.I., MIRKH; Ariansyah; Datu Permana, Datu Permana (STAI DDI Makassar, 2023)
The progress of Western civilization's hegemony cannot be separated from the role of Muslim scientists in developing knowledge and science. But on the other hand, when Western scholars develop and apply the theories of Muslim scientists, they reject the Islamic values ​​contained therein. Therefore, this research aims to examine the concept of Islamization developed by al-Khwarizmi, a Muslim scientist who played an important role in the development of modern mathematics. The Islamic values ​​developed by Al-Khwarizmi can be seen in his discoveries, especially in the fields of algebra, arithmetic, algorithms, geography and others. This research uses library research by collecting data through books and journals, using descriptive methods and a systematic approach. The results of the research found that the Islamization values ​​developed by Al-Khwarizmi were the result of his tadabbur and tafakkur on the verses of the Koran. an which talks about roseits, determining days and months, and understanding the Qudsi hadith which talks about nothingness and contributed to determining the latitude and longitude of areas conquered by Islam during the Abbasid era under the Al-Makmun caliphate.